A new endemic Ramalina species from the Canary Islands (Ascomycota, Lecanorales) - Pérez-Vargas, Israel (Phytotaxa, 2014)
Ramalina alisiosae (Ramalinaceae), found on trees in the laurel forests of the Canary Islands is described as new to science. A description of the species is given together with notes on its chemistry, distribution, ecology, and taxonomy. Bayesian and Maximum Likelihood analyses of ITS sequences showed a close relation of the new species with R. implectens and R. farinacea. Morphological and anatomical differences with these related lichen taxa are discussed.